Thermally-Activated Vortex Motion and Electrical Dissipation in a Bi 2 Sr 2 CaCu 2 Oδ Thin Film - C. R. de la Cruz; A. P. C. dela Cruz; L. J. D. Guerra; R. V. Sarmago (Science Diliman, 2003)
The magnetoresistance, obtained from resistivity measurements with external magnetic fields up to 0.5T,was used to directly measure and investigate the electrical dissipation properties of a c-axis orientedBi2Sr2CaCu2O8+δ thin film. An activation-related “peaked” profile below Tc was observed in themagnetoresistance. In increasing applied magnetic field, the peak shifts to lower temperatures, broadens,and becomes more asymmetric. The analysis, made based on an Arrhenius-type activation mechanism,shows that the activation energy decreased with increasing applied magnetic field, as predicted by theAnderson-Kim Thermally-Activated Flux Creep Theory. Therefore, in these low magnetic fields andtemperatures, the vortex motion predominant in the films is thermally activated and contributes largely tothe dissipation in these films.